2020
DOI: 10.5144/0256-4947.2020.298
|View full text |Cite
|
Sign up to set email alerts
|

One-year postoperative mortality rate among the elderly with hip fractures at a single tertiary care center

Abstract: BACKGROUND: Hip fractures are one of the leading causes of disability and dependency among the elderly. The rate of hip fractures has been progressively increasing due to the continuing increase in average life expectancy. Surgical intervention is the mainstay of treatment, but with an increasing prevalence of comorbid conditions and decreased functional capacity in elderly patients, more patients are prone to postoperative complications. OBJECTIVES: As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Studies have shown that a high ASA score is associated with mortality (23)(24)(25)(26). The high ASA values in our study group support the literature.…”
Section: Most Patients With Hip Fractures Are Of Advanced Age (2)supporting
confidence: 90%
“…Studies have shown that a high ASA score is associated with mortality (23)(24)(25)(26). The high ASA values in our study group support the literature.…”
Section: Most Patients With Hip Fractures Are Of Advanced Age (2)supporting
confidence: 90%
“…Each of these procedures has disadvantages, such as femoral nerve damage, hemorrhage, dural puncture headache, and so on. With the advancement of peripheral nerve block technology, FICB has become commonly utilized for postoperative analgesia in patients having hip, femur, and knee surgery [20]. The lateral femoral cutaneous nerve and the obturator nerve have a good success rate.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in another study was done by Alsheikh KA, et al, in which data collected from patient's records between 2008 and 2018 for patient's undergoing hip surgeries, the intra-operative and post-operative complications were 3% and 16%, respectively. 4% died within 30 days, and 11% died within one year [35] .…”
Section: Sensitivitymentioning
confidence: 97%